Initial Surface Absorption of Cement Combination Concrete - Samuel Olufemi Folagbade (Civil Engineering Dimension, 2018)
This paper investigated the initial surface absorption (ISAT) of concrete using Portland cement (PC) and some binary and ternary cement combinations containing fly ash (FA), silica fume (SF) and metakaolin (MK) as partial replacements for PC at equal water/ cement ratios and strengths. At equal water/cement ratios, the cement combination concretes have higher ISAT values than PC concrete at 28 days and the disparity reduced with increasing curing age due to improved pozzolanic reactivity of the supplementary cementitious materials. SF and MK as binary and ternary cement components performed better than FA due to their higher fineness, improved particle packing and higher pozzolanic reactivity. At equal strengths, FA binary cement concretes have the lowest ISAT values and these reduced with increasing content of FA. At total replacement levels more than 20%, all the ternary cement concretes have lower ISAT values than PC concrete and the values reduced with increasing total replacement level due to the beneficial effect of FA.